Peran Ganda Media Sosial dalam Penegakan Hukum Indonesia: Analisis Sosio-Legal antara Peluang Transparansi dan Risiko Erosi Due Process - Irwan Triadi; Febrian Rizky Akbar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This socio-legal study analyzes the dual role of social media in Indonesia's criminal justice system from 2019 to 2024 through thematic analysis of 15 viral legal cases. The research demonstrates that while social media enhances transparency and accelerates investigations in 80% of cases examined, it simultaneously erodes fundamental due process principles in 53% of cases through trial by social media and digital vigilantism. The phenomenon of